A method to determine the constitutive parameters of oxide in accelerated corrosion tests of reinforced concrete specimens. (November 2017) - Sanz, Beatriz; Planas, Jaime; Sancho, José M.
Abstract: A novel methodology was developed for indirect determination of the mechanical parameters of the oxide in reinforced concrete corrosion, with satisfactory results. It combines accelerated corrosion tests performed over concrete prisms cast around a steel tube equipped with special instruments, and numerical simulations using a model that reproduces the oxide expansion and its mechanical behavior, and fracture of concrete by means of the cohesive crack model. In this work, systematization for determining the values of the oxide parameters is proposed, and strong verification of the method is provided by presenting the results of an extensive experimental campaign. Highlights: A method is presented to determine the mechanical parameters of the oxide layer. Accelerated corrosion of prisms with a steel tube specially instrumented is simulated. Values for the oxide parameters are proposed to be used in other models. For a critical analysis of the method a numerical analysis has been carried out. An extensive experimental campaign has verified the proposed values and the method.